Re-evaluating what we "know" about female athletes in biomechanics research: across the continuum from capacity to skill - Nimphius, S. (ISBS Proceedings Archive (Michigan), 2018)
Data from recent research around gender bias as a result of lack of control for physical capacity measures or skill assessment. Research data and case studies will be used to determine if we really "know" what we`ve said about the biomechanics of female athletes and what we might consider when putting forward recommendations based on these conclusions. The overall premise will be to remind ourselves as sports biomechanists that although we should have an expertise, we need to also be an excellent generalist to do our job well, especially in the applied environment where we see bias on both ends of the spectrum from "capacity" focused to "performance" focused research. Examples of going from biomechanics to S&C will be provided as well as a justification why our biomechanics research needs to extend athlete characteristics beyond just "gender, height, weight and age".